Atomic model of the papillomavirus capsid - Modis, Yorgo (Oxford University Press, 2002)
Papillomaviruses propagate in differentiating skin cells, and certain types are responsible for the onset of cervical cancer. We have combined image reconstructions from electron cryomicroscopy (cryoEM) of bovine papillomavirus at 9 Å resolution with coordinates from the crystal structure of small virus-like particles of the human papillomavirus type 16 L1 protein to generate an atomic model of the virion. The overall fit of the L1 model into the cryoEM map is excellent, but residues 402–446 in the ‘C-terminal arm’ must be rebuilt. We propose a detailed model for the structure of this arm, based on two constraints: the presence of an intermolecular disulfide bond linking residues 175 and 428, and the clear identification of a feature in the image reconstruction corresponding to an α-helix near the C-terminus of L1. We have confirmed the presence of the disulfide bond by mass spectrometry. Our ‘invading arm’ model shows that papilloma- and polyomaviruses have a conserved capsid architecture. Most of the rebuilt C-terminal arm is exposed on the viral surface; it is likely to have a role in infection and in immunogenicity.